Konsep Ilmu Ladunni dalam Upaya Penafsiran Al-Quran - Abdul Muid Nawawi; Abdul Rouf; Hasanuddin Hasanuddin (Institut PTIQ Jakarta, 2019)
Ladunni’s science becomes an inseparable part and becomes a necessity. Thus, the Ladunni Science demonstrates the importance of its role in the interpretation of the Qur’an and the importance of understanding this type of scholarship (science of Ladunni) for the exegetes. In textual matters, the Ladunni Science functionally has two main working areas, namely the text area (object or internal) and the review region (subject or external). In the discourse of tafseer, the text is the Qur’an and the reviewer is the mufassir (as well as the reader). This thesis also found three functions, contributing to the text of the Qur’an, namely: a. Reveals the inner things (asrar) of the object; b. Achieves the highest point of human effort in understanding texts and objects, and c. Avoid inaccurate understanding and meaning of a text or object. While the function of the mufassir also there are three, namely: a. As moral control for the perpetrators, b. Showing His greatness and power at the same time reveals the limitations of the subject’s ability, and c. Ma’rifat bi-l was